Mahfouz’s The Beggar, Mirror of a Changing Society : Analysis of a Cinematic Adaptation (مجلة إحالات, 2026)
This article presents an in-depth analysis of the cinematic adaptation of Naguib Mahfouz’snovel "The Beggar" (Al-Shahhat), directed by Houssam Eddine Mostafa in 1973. The study examinesthe artistic challenges of translating a philosophically introspective literary work into film, highlighting the narrative and thematic transformations from novel to screen. It explores howexistential and nihilistic themes evolve in the adaptation process, with the film introducing explicitsociopolitical dimensions absent from the original novel. The article also focuses on the symbolicrepresentation of female characters and their role in reflecting the tension between tradition andmodernity in Egyptian society. Ultimately, the film is shown to offer a visually compelling interpretation of the protagonist’s existential crisis, mirroring the complexities of identity and the search for meaning in post-revolutionary Egypt.